Recovery of Love wave overtone waveforms and dispersion curves from single-station seismograms using time-warping. Issue 1 (8th February 2022) - Brown, M G; Lin, G; Matsuzawa, H; Yoshizawa, K
SUMMARY: Time-warping is a signal processing technique that, when applied to an isolated measurement of a transient signal that propagates in a waveguide, allows contributions to that signal from individual mode numbers to be isolated and extracted. Dispersion curves for individual mode numbers can, in turn, be recovered. Isolation of contributions associated with individual mode numbers is possible because after time-warping—a special environmentally dependent non-uniform sampling—is applied, the signal energy corresponding to each mode number is isolated in the frequency spectrum of the time-warped signal. Here we derive the time-warping transform for teleseismic Love waves, assuming the Earth structure is approximately known, and we illustrate the utility of time-warping using both synthetic and measured seismograms.